EFISIENSI PEMBEBANAN PLTGU PT. KRAKATAU DAYA LISTRIK DENGAN PERHITUNGAN SPECIFIC FUEL CONSUMTION UNTUK MEMINIMALKAN BIAYA PRODUKSI LISTRIK - Budi Santoso; Muchamad Nur Qosim; Fahmi Abdul Ajiz (Sekolah Tinggi Teknik - PLN, 2015)
PT. Krakatau daya listirk (KDL) is a company engaged in the electrical power plant. Krakatau Daya Listrik power plant has a capacity of 3X40 MW that operate with natural gasfuel. Electrical production of PT. Krakatau Daya Listrik used to supply electricity to the entire industrial area of Krakatau, which is biggest customers is PT. Krakatau Stell (KS), Electrical supply from PT. Krakatau Daya Listrik Used to operate PT. Krakatau Stell for electrical arc furnace. The steel smelting process required enormous power and fluctuate greatly, resulting in a loadchange that varies greatly in Krakatau Daya Plant. The load change can affect and Krakatau Daya Listrik Power plant efficiency, it is the increase in powerplant fuel consumtion. This paper will calculated the fuel that influenced by the changes of power plant efficiency of PT. Krakatau Daya Listrik.